2000
DOI: 10.1105/tpc.12.9.1679
|View full text |Cite
|
Sign up to set email alerts
|

Association of Phosphatidylinositol 3-Kinase with Nuclear Transcription Sites in Higher Plants

Abstract: The kinases responsible for phosphorylation of inositol-containing lipids are essential for many aspects of normal eukaryotic cell function. Genetic and biochemical studies have established that the phosphatidylinositol (PtdIns) 3-kinase encoded by the yeast VPS34 gene is essential for the efficient sorting and delivery of proteins to the vacuole; the kinase encoded by the human VPS34 homolog has been equally implicated in the control of intracellular vesicle traffic. The plant VPS34 homolog also is required f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
40
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(40 citation statements)
references
References 32 publications
(32 reference statements)
0
40
0
Order By: Relevance
“…It has been suggested that PtdIns(3)P is involved in intracellular vesicle trafficking by binding to the FYVE domain [11,21]. Bunney et al demonstrated that PtdIns 3-kinase is associated with active nuclear or nucleolar transcription sites, suggesting a role in the regulating transcription [27]. It was also reported that ABA-induced ROS production in guard cells, involved in stomatal closure, is inhibited by the PtdIns 3-kinase inhibitors wortmannin and LY294002 [28].…”
Section: Discussionmentioning
confidence: 93%
“…It has been suggested that PtdIns(3)P is involved in intracellular vesicle trafficking by binding to the FYVE domain [11,21]. Bunney et al demonstrated that PtdIns 3-kinase is associated with active nuclear or nucleolar transcription sites, suggesting a role in the regulating transcription [27]. It was also reported that ABA-induced ROS production in guard cells, involved in stomatal closure, is inhibited by the PtdIns 3-kinase inhibitors wortmannin and LY294002 [28].…”
Section: Discussionmentioning
confidence: 93%
“…Nuclear PtdIns(3)P has been reported in BHK cells and human fibroblasts by the use of FYVE domain probes (Gillooly et al, 2000), and in HL-60 cells, PtdIns(3)P level increases at G2/M phase of the cell cycle (Visnjic et al, 2003). In plants, PI3K is associated with active nuclear and nucleolar transcription sites (Bunney et al, 2000), and some of the proteins with a FYVE domain have regulator of chromosome condensation 1 tandem repeats, known to be important in nuclear processes (Drøbak and Heras, 2002). Therefore, the control of DNA replication or transcription is a possible mechanism for PI3K regulation of the cell cycle.…”
Section: Discussionmentioning
confidence: 99%
“…It is essential for normal growth, as demonstrated by the expression of AtVPS34 antisense constructs, which leads to second-generation transformed plants with very severe defects in growth and development (Welters et al, 1994). Plant PI3K is associated with active nuclear and nucleolar transcription sites (Bunney et al, 2000), which led to the suggestion that it plays a role in active transcription. Together with the fact that there is no other enzyme that can produce PtdIns(3)P, a lipid with many physiological effects in plants, these reports indicate that Vps34p-like PI3K has much broader functions in plants than in animals or budding yeast.…”
mentioning
confidence: 99%
“…These requirements are met by the roots and florets and other organs of many plants. We have used it for both roots and florets of wheat (Triticum aestivum L.) and related species [1][2][3] , for rye (Secale cereale L.) florets 4 , for rice (Oryza sativa L.) roots and florets 5 and maize (Zea mays L.) roots 6 among the cereals, and for roots of pea (Pisum sativum L.), bean (Vicia faba L.) 7 and soya (Glycine max L.) 8 . The only plant species with which we have been unsuccessful in vibratome sectioning is Arabidopsis thaliana, because of its small size.…”
Section: Introductionmentioning
confidence: 99%
“…The resulting vibratome sections can be used in many different types of labeling experiments. We have used such sections for DNA FISH, for RNA FISH to detect transcripts 10 , for antibody immunofluorescence labeling 8 and for labeling of nascent transcripts by BrUTP incorporation in unfixed tissue. We have also combined antibody and BrUTP labeling with FISH (e.g., ref.…”
Section: Introductionmentioning
confidence: 99%